2017
DOI: 10.1123/jtpe.2016-0059
|View full text |Cite
|
Sign up to set email alerts
|

Using Content Maps to Measure Content Development in Physical Education: Validation and Application

Abstract: Purpose:This study reports on our efforts toward extending the conceptual understanding of content development in physical education by validating content maps as a measurement tool, examining new categories of instructional tasks to describe content development and validating formulae that can be used to evaluate depth of content development.Method:The reliability, content, and concurrent validity of content maps and formulae were evaluated together with an application of the content maps and formulae. Descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 6 publications
0
49
0
Order By: Relevance
“…The validity, reliability, and concurrent validity of this measure have been previously established in differentiating between weak and strong SCK among teachers (Ward et al, 2017). Ward et al (2017) found that an SCK index score "3" is a cut-point which distinguishes between weak and strong SCK of teachers. A score three represents content development by a teacher that is three progressions beyond the initial task taught to the students.…”
Section: Instrumentmentioning
confidence: 98%
See 1 more Smart Citation
“…The validity, reliability, and concurrent validity of this measure have been previously established in differentiating between weak and strong SCK among teachers (Ward et al, 2017). Ward et al (2017) found that an SCK index score "3" is a cut-point which distinguishes between weak and strong SCK of teachers. A score three represents content development by a teacher that is three progressions beyond the initial task taught to the students.…”
Section: Instrumentmentioning
confidence: 98%
“…Content maps were used to measure the SCK of participants (the detailed description of content maps can be found in Ward, Lehwald, and Lee, 2015). Content maps have been validated in a number of studies (Tsuda et al, 2019;Ward et al, 2018;Ward et al, 2017). A content map is a graphic organizer of SCK that defines the content that could be taught to students in an instructional unit of a particular duration (e.g., 5, 10, or 20 lessons; Ward et al, 2015).…”
Section: Instrumentmentioning
confidence: 99%
“…The selection and sequencing of instructional tasks, called content development or content progression, in a developmentally appropriate way so that students achieve an instructional outcome is a critical skill in teaching (Ball, Thames, & Phelps, 2008;Rink, 2009;Siedentop & Tannehill, 2000;Ward, 2013;Ward et al, 2017). Effective teaching is characterized by the development of content that moves students through simple to complex learning experiences towards a higher level of competency (Rink, 2006;Rink & Hall, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Applying tasks focus on a student's ability to apply the performance in a particular context such as a game or it can be used as an assessment of student performance. Given the widespread development and implementation of instructional models using small sided games such as Teaching Games for Understanding (Griffin & Butler, 2005), Play Practice (Launder & Piltz, 2013) and Sport Education (Siedentop, Hastie, & van der Mars, 2011), Ward et al (2017) refined Rink's initial categories to describe content development within games more precisely by creating four additional tasks: extending-applying, refining-applying, applying-nongame and applying-game tasks. Extending-applying and refining-applying tasks are extending and refining tasks that occur in the context of small sided games or that might be used when teaching in a game.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation